EVALUASI KERUSAKAN BANGUNAN AKIBAT GEMPA BESAR - Tamara, Max (Sam Ratulangi University, 2011)
Earthquake performance of Reinforced Concrete construction has been well documented. Damage patterns in reinforced concrete during the 1971 San Fernando (California) earthquake have been extensively studied. More recently, several destructive earthquakes of the last decade. These earthquakes have revealed the following patterns of damages and failures in Reinforced Concrete construction. Shear failure and concrete crushing failure in concrete columns, partial ductile design and detailing, conceptual design deficiencies, inappropriate column/beam relative strengths, inadequate detailing, soft-story effects and short-column effects.Keywords: Earthquake performance, damage pattern, shear failure, crushing failure, soft-story effects, short-column effects